Audit of childhood diabetes control in Indonesia - Jose RL Batubara (Paediatrica Indonesiana, 2002)
Objectives To detennine the status of diabetes control in children and adolescents in Indonesia.Methods We collected data from seven pediatric diabetes centers in Indonesia from January to September 2001. Data were obtained either by patient interview during the enrollment visit or by reviewing medical records of the most recent clinical examination and treatment infonnation. Blood samples were also collected for the assessment of HbA1 c.Results Most patients recruited had type 1 diabetes (n=64, 93%) and the focus of this report was on this group. The mean of centrally measured HbA1C in the 60 type 1 patients was 10.5 (SO 2.7%) with 90% having values exceeding 7.5%, indicating inadequate glycemic control. The mean HbA1c was higher in patients older than 10 years but not necessarily in children with longer diabetes duration or older age of diabetes onset. The frequency of severe hypoglycemic or diabetic ketoacidosis was 75 and 20 per 100 patient-years, respectively. Severe hypoglycemia was higher in children younger than five years than those older. Chronic complications including microalbuminuria, neuropathy and retinopathy, were reported in older children but not necessarily in children with longer duration of diabetes or earlier age of diabetes onset. Glycemic control tended to be better for patients on thrice rather than twice daily insulin injections. However, only 12% were on three or four times daily insulin injection regimen compared to 88% who were on twice daily insulin injections.Conclusions The present audit shows that 90% of the type 1 and all of the type 2 patients did not achieve adequate glycemic control (HbA1c >7.5%). The frequency of severe hypoglycemia was higher in the younger children and glycemic control was worse in the older children.Â